INVASIVE PHYSICAL THERAPY AND DRY NEEDLING. REPORT ON THE EFFECTIVENESS OF DRY NEEDLING IN THE TREATMENT OF MYOFASCIAL PAIN SYNDROME AND ITS USE IN PHYSICAL THERAPY - Mayoral-del Moral, O; Torres-Lacomba, M (Cuestiones de Fisioterapia, 2009)
«Invasive Physical Therapy» is an expression coined to mean the set of techniques in which the physical agent used to treat some conditions penetrates the patient's skin. When the physical agent used for the treatment of certain neuromusculosqueletal conditions is only the mechanical stimulation of different types of needles, Invasive Physical Therapy technique is called dry needling, normally used for the treatment of myofascial pain syndrome. Sometimes the use of dry needling by physical therapists is controversial. In this sense, this report aims to present the current evidence regarding dry needling, as well as highlighting the appropriateness of the use and the inclusion of the expression «Invasive Physical Therapy» in all those documents that could be used as a basis for regulating the professional competences of physical therapists